Polyhydroxyalkanoates as biomaterials - Bhagyashri, S.; Gadgil, Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2017)
Polyhydroxyalkanoates (PHAs) are biopolymers synthesized by bacteria under unbalanced growth conditions. These biopolymers are considered as potential biomaterials for future applications because they are biocompatible, biodegradable, and easy to produce and functionalize with strong mechanical strength. Currently, PHAs are being extensively innovated for biomedical applications due to their prerequisite properties. The wide range of biomedical applications includes drug delivery systems, implants, tissue engineering, scaffolds, artificial organ constructs, etc. In this article we review the utility of PHAs in various forms (bulk/nano) for biomedical applications so as to bring about the future vision for PHAs as biomaterials for the advancement of research and technology.
Keywords: Biomedical Applications; Cancer-therapy; Drug-delivery Systems; In-vitro; Molecular-weight; Poly(Ester Urethane)S; poly(ethylene glycol); Regenerative Medicine; Tissue Engineering Applications; Vitro Antibiotic Release

Synthesis and characterization of biocompatible poly (L-lactide) using zinc (II) salen complex - Rade, Priyanka P.; Garnaik, Baijayantimala (International Journal of Polymer Analysis and Characterization, 2020)
A biocompatible zinc (II) complex based on a tetradentate N,N,O,O-type salen ligand was synthesized, characterized and used for the solvent-free ring-opening polymerization (ROP) of L-lactide in bulk at 180 degrees C to prepare high molecular weight poly(L-lactide) (M-n: 82,600 Da;M-w: 140,000 Da; PDI: 1.70). Poly(L-lactide) (PLLA) was characterized using FTIR,H-1 NMR,C-13 NMR, GPC, TGA, DSC, WAXD, and MALDI-ToF. Kinetic measurement was carried out and first-order behavior to monomer was observed. Thek(app)was found as 6 +/- 0.001 x 10(-4 )s(-1). The biocompatibility of the PLLA was confirmed byin vitrocytotoxicity against NIH/3T3 fibroblast cell line and can be used in biomedical applications.
Keywords: Biocompatible; Biomedical Applications; in vitro; PLLA; zinc (II) salen complex

Controlled synthesis of thermosensitive tunable porous film of (pNIPAM)-b-(PCL) copolymer for sustain drug delivery - Amgoth, Chander; Patra, Sukanya; Wasnik, Kirti; Maity, Pradip; Paik, Pradip (Journal of Applied Polymer Science, 2023)
There have been reports on different types of porous polymer films for various applications. The designing of such porous films with uniform properties is a challenging task. In this work, tunable porous thin films of poly(N-isopropylacrylamide) (pNIPAM) and polycaprolactone (PCL), that is, (pNIPAM)-b-(PCL) has been fabricated and its sustained drug delivery applications have been reported. First, the (pNIPAM)-b-(PCL) has been synthesized through the addition polymerization of pNIPAM and PCL. Then the synthesized (pNIPAM)-b(PCL) has been used to design porous thin film with varying temperatures without using any external template, below and above the lower critical solution temperatures (LCST) of pNIPAM. Pore size in (pNIPAM)-b-(PCL) films has been tuned by varying the temperature from similar to 10 to 40 degrees C. Then the developed thermosensitive porous film has been taken and seeded with the K562 (chronic myeloid leukemia blood cancer) and HepG2 (hepatocarcinoma) cells and the skin cancer cells (B16-F10) killing efficiency of anticancer drug (e.g., doxorubicin hydrochloride, DOX) loaded (pNIPAM)-b-(PCL) film has been studied. It is found that the DOX-loaded (pNIPAM)-b-(PCL) can efficiently kill the skin cancer cells. The porous polymer thin film reported in this work can be a versatile platform for the loading of drugs and it can be used for the various therapeutic applications.
Keywords: Biomaterials; Biomedical Applications; drug delivery systems; films; nanostructured polymers